Purchase intention of Sariayu cosmetics among Muslim university students as viewed from green product and product quality: An Islamic economic perspective - Yati, Fenni Windi; Syahbudi, Muhammad; Harahap, Muhammad Ikhsan (Universitas Islam Indonesia, 2024)
IntroductionThe worsening environmental conditions motivate beauty industries to pay attention to ecological aspects in running their businesses, namely creating environmentally friendly (green products) of good quality. ObjectivesThis study aimed to determine whether green products and quality affect purchase intention.MethodThe research method used is a quantitative approach. The population was female students of the Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sumatera Utara Medan, and the sample size was 98 respondents. The analysis technique in the study used multiple linear regression, and the data was processed using SPSS.ResultsThe results showed that the green product and product quality together positively affected purchase intention.ImplicationsThis research provided insights for the beauty industry to enhance their involvement in environmentally friendly products without neglecting their quality.Originality/NoveltyThis study contributes to enriching studies on halal cosmetics among Muslim consumers from an Islamic perspective in Indonesia.